Mediating Johann Georg Zimmermann's Von der Erfahrung in France and Britain - Tarkka, Laura; Mannweiler, Caroline (Routledge, 2025)
In the 1770s, the Swiss physician Johann Georg Zimmermann's medical writings, notably his widely known Von der Erfahrung in der Arzneykunst [On Experience in Medicine] (1763), were introduced to British and French readers via four translations. In the first, A Treatise on the Dysentery [Von der Ruhr] (1771 [1767]), the translator Charles Rivington Hopson M.D. observed that Zimmermann was not only an esteemed physician but also a first-class ‘German writer’ indulging in ‘high flights of metaphorical expression’. To see how contemporaries dealt with a ‘philosophical’ doctor who stressed the importance of careful observations and yet did not hesitate to use imaginative rhetoric to guide the reason of his readers, this chapter compares the translation choices made by Jean-Baptiste Lefebvre de Villebrune M.D. in Traité de l’expérience (1774) and an anonymous translator in A Treatise on Experience in Physic (1778). Since Villebrune also translated Von der Ruhr as Traité de la dyssenterie [sic] in 1775, Hopson's earlier translation serves as a further point of comparison. Our aim is to establish how Zimmermann's works – which connected medical reasoning with patriotic sentiment and policy-making – were adapted to readers who worked in different polities.
Translating Science in the 18th and 19th Centuries: Interdisciplinary Perspectives